Jugaad Culture Amidst COVID-19: A Time to Step Up for Innovation in Low-Income Countries - Baral, Suman (Journal of Lumbini Medical College, 2020)
More than four months have already elapsed after the world first encountered Coronavirus claimed to originate from Wuhan, China. Scientifically, termed sudden acute respiratory syndrome corona virus (SARS-CoV-2), that causes Coronavirus disease of 2019 (COVID-19), this deadly pathogen has already claimed about 2.83 lakhs casualties with four million infected and 1.5 million recovered as of 11 May 2020. Different preventive measures like hand washing, social distancing, nation-wide lock down from March 23 have been practised in Nepal which has definitely dwindled the number of positive cases. they have helped flatten the curve and procure time for preparation for forthcoming disaster. Total documented positive cases have been 120 till date (11 May 2020) with zero mortality in Nepal. However, the scenario might be out of control in coming days where claims of inadequate testing due to lack of diagnostic kits have been a major issue. Whatever be the outcome in upcoming days, for an economically poor country like Nepal, preparation seems satisfactory despite challenges to outsourcing the necessary kits like Personal Protective Equipment (PPE) and diagnostic Polymerase Chain Reaction (PCR) machines etc.